Implementasi Perda Nomor. 2 Tahun 2008 Terhadap Pemenuhan Hak Anak Jalanan - Bakhtiar Bakhtiar; Ahmad Jamalong; Annisa Nurul Awalia (Jurnal Tomalebbi, 2025)
1) The mechanism for implementing the Makassar City Government Policy on the Fulfillment of the Rights of Street Children consists of 2 coachings, namely Prevention and Follow-up Development. Prevention Coaching consists of: a. Data Collection, b. Monitoring, Control, and Supervision, c. Socialization and Campaigns and Further Coaching consist of: a. Protection and Control at Any Time, b. Temporary Shelter, c. Initial Approach, Disclosure, and Problem Understanding (Assessment), and d. Social Assistance and Referral 2) The impact of the Makassar City Government's policies in fulfilling the rights of street children, namely: The influence of the Social Servies development program for street children has not shown optimal results so that street children are still carrying out activities on the streets. 3) Obstacles of the Makassar City Government in Fulfilling the Rights of Street Children include: Lack of Facilities and Infrastructure, Lack of Human Resources, Inadequate Budget, No Regulatory Updates, and Lack of Awareness of Street Children's Families and the Community.